An experimental study on the influence of instructional mobile applications in enhancing listening comprehension of rural students in India - Raj, Antony; Tomy, Prajeesh (Frontiers in Education, 2024)
Introduction Mobile learning (M-learning) is integral to language education, offering accessibility, portability, and diverse resources. It offers real-life language use with synchronous learning, flexibility, and an opportunity to engage with the global community. It allows learners to practice language skills from anywhere. This study aims to evaluate linguistic instructional mobile applications' effectiveness on listening comprehension among Indian rural students. Methods Pedagogic mobile applications were employed in an experimental study with 149 tertiary-level students from rural colleges in Tamil Nadu, India. Participants were divided into control (n = 75) and experimental (n = 74) groups. Pre and post-tests assessed listening comprehension levels, considering demographic variables. Different types of audio files were used in the intervention to improve the listening skills of the experimental group. Results Statistical analyses, including paired t-tests, independent t-tests, and ANOVA, revealed significant improvement in listening skills for the experimental group. Gender, locality, and parental income were considered as significant variables, showing that students from diverse backgrounds benefited from mobile applications. Discussion The results indicate that M-learning effectively aids rural students in overcoming language barriers, emphasizing the potential of mobile applications in language education.